2016
DOI: 10.1038/srep37944
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the microbial derived short chain fatty acid propionate on host susceptibility to bacterial and fungal infections in vivo

Abstract: Short chain fatty acids (SCFAs) produced by intestinal microbes mediate anti-inflammatory effects, but whether they impact on antimicrobial host defenses remains largely unknown. This is of particular concern in light of the attractiveness of developing SCFA-mediated therapies and considering that SCFAs work as inhibitors of histone deacetylases which are known to interfere with host defenses. Here we show that propionate, one of the main SCFAs, dampens the response of innate immune cells to microbial stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(77 citation statements)
references
References 83 publications
3
74
0
Order By: Relevance
“…Real-time PCR was conducted using the Fast SYBR® Green Master Mix and a QuantStudio™ 12 K Flex system (Life Technologies, Carlsbad, CA) 44, 45 . Primers have been described 45, 51 .…”
Section: Methodsmentioning
confidence: 99%
“…Real-time PCR was conducted using the Fast SYBR® Green Master Mix and a QuantStudio™ 12 K Flex system (Life Technologies, Carlsbad, CA) 44, 45 . Primers have been described 45, 51 .…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the gut microbiota was shown to provide several cofactors needed for enzymes involved in epigenetic modifications such as acetyl‐CoA and NAD + . For histone‐deacetylases (HDAC) in particular, gut microbiome‐derived short‐chain fatty acids such as butyrate or propionate were shown to be key regulators of activity , which in turn can have many downstream effects in mediating human disease, such as type 2 diabetes or obesity . One key mechanism by which the microbiome regulates host circadian transcriptomic oscillations is through the modulation of the chromatin landscapes.…”
Section: Mechanisms Of Circadian Host–microbiome Crosstalkmentioning
confidence: 99%
“…Interestingly, it has also been suggested that the production of propionate by intestinal microflora may be a protective mechanism to control the host response to commensals. This way, the host would avoid local inflammation and tissue damage [66].…”
Section: Propionate Metabolism As An Antimicrobial Targetmentioning
confidence: 99%